Bogotá experience in government: device and educational strategies to expressions, scenarios and breaks on a proposal for citizen culture - Gloria Clemencia VALENCIA GONZÁLEZ; Lilia CAÑÓN FLÓREZ; Carlos Alberto MOLINA RODRÍGUEZ (Ediciones Universidad de Salamanca, 2012)
The Bogotá currently known, rebuilt from the ashes of 9 April got used for decades to live labors, fear and mistrust, but particularly in exclusion. With the arrival of Antanas Mockus to Mayor broke various paradigms: he and his cabinet not came from the traditional political caste, came from the Academy and claimed other relationships with citizenship. In addition, became the city learning space because their Government project drew on the political but evidenced in the pedagogical and found its deployment in the communicative. Six priorities proposed for government experience are articulated around one: civic culture. Culture that should be disseminated, learned and implementation from train in town, then so is generate sense of belonging, would facilitate urban coexistence and would lead to the respect of the common heritage and recognition of the rights and duties of citizens. In the Mayor Mockus's «great classroom» citizenship would of apathy to the habitancia. Far pedagogy and communication, as not nominated devices, managed to go beyond the labelling and the indication and approached the civic culture to political socialization? This reflection article links to research «higher education and training citizen, case Bogotá» and consists of five sections.